2018
DOI: 10.1186/s40101-018-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal differences in brown adipose tissue density and pulse rate variability in a thermoneutral environment

Abstract: BackgroundBrown adipose tissue (BAT) is sympathetically activated and induces thermogenesis during cold exposure, thereby influencing energy expenditure and body fat levels. The very low frequency (VLF) components of pulse rate variability could be a form of thermogenic sympathetic nervous activity, but no clear relationship has yet been reported between VLF activity and BAT density. We therefore aimed to evaluate the association between them.MethodsWe enrolled 20 adults in winter and 20 matched adults in summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…We showed that body fatness parameters were negatively correlated with BAT-d, which is consistent with the results of various studies that used 18 FDG-PET∕CT, regardless of the presence of cold exposure. 6,[14][15][16][17]19,20 Although we should consider the possibility that the BAT-d was affected by subcutaneous fat thickness, 26 the subcutaneous fat thickness in the supraclavicular region is within a very narrow range and has little effect on the measured parameters. For instance, the fat thickness in the supraclavicular region ranged from 0.6 to 2.5 mm when evaluated by B-mode ultrasonography in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that body fatness parameters were negatively correlated with BAT-d, which is consistent with the results of various studies that used 18 FDG-PET∕CT, regardless of the presence of cold exposure. 6,[14][15][16][17]19,20 Although we should consider the possibility that the BAT-d was affected by subcutaneous fat thickness, 26 the subcutaneous fat thickness in the supraclavicular region is within a very narrow range and has little effect on the measured parameters. For instance, the fat thickness in the supraclavicular region ranged from 0.6 to 2.5 mm when evaluated by B-mode ultrasonography in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The probes were placed on the skin of the supraclavicular region that potentially contained BAT, and participants were required to remain in a sitting position during the measurements, as previously described. [23][24][25][26] Compared with visible light wavelengths, NIR wavelengths (700 to 3000 nm) show lesser scattering and, consequently, better penetration into biological tissue. However, light absorption by water limits tissue penetration above the 900-nm wavelength; thus, the 650-to 900-nm range is suitable for measurements.…”
Section: Brown Adipose Tissue Density Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies revealed that an increase in BAT activity induced by repeated ingestion of thermogenic food ingredients can be detected by an increase in [Total-Hb] [40]. Collectively, [Total-Hb] in the supraclavicular region evaluated by NIR TRS is expected to be suitable for evaluating BAT density (BAT-d) and equivalent to the determination of BAT activity or BAT volume by 18 FDG-PET/CT using cold exposure [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Among the Yakut, a population that is indigenous to northeastern Siberia, adults with greater BAT thermogenesis expend more energy during acute cold stress (Levy et al, ). Additionally, populations living in temperate zones increase their BAT metabolism in response to repeated cold exposure and exhibit seasonal changes in BAT mass (Nirengi et al, ; van der Lans et al, ). By building on this work, future investigations of BAT may shed light on the evolution of human biological adaptations.…”
Section: Introduction: Why Measure Bat?mentioning
confidence: 99%